2016
DOI: 10.5194/acp-16-4119-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric speciated mercury concentrations on an island between China and Korea: sources and transport pathways

Abstract: Abstract. As a global pollutant, mercury (Hg) is of particular concern in East Asia, where anthropogenic emissions are the largest. In this study, speciated Hg concentrations were measured on Yongheung Island, the westernmost island in Korea, located between China and the Korean mainland to identify the importance of local and regional Hg sources. Various tools including correlations with other pollutants, conditional probability function, and back-trajectory-based analysis consistently indicated that Korean s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 74 publications
1
6
1
Order By: Relevance
“…The mean concentrations (±1σ) of GEM, GOM, and PBM 2.5 during the entire observation period from the year 2007 to 2018 were 1.81 ± 0.43 ng m −3 (hourly mean values for 5 min intervals, N = 53,840), 1.7 ± 2.9 pg m −3 (N = 22,071) and 2.6 ± 3.6 pg m −3 (N = 22,058), respectively (Table 1). The mean GEM concentrations were lower than those reported for urban, suburban, and remote sites in the East Asian region [15,[42][43][44][45], but were slightly higher than the background concentrations recorded in the Northern hemisphere (1.3-1.6 ng m −3 ) and in the Southern hemisphere (around 1.0 ng m −3 ) [14,46]. Thus, it was inferred that the concentrations of Hg at Cape Hedo were elevated due to regional pollution because there are no local Hg stationary emission sources around this site.…”
Section: Concentrations Of Gem Gom and Pbm 25contrasting
confidence: 59%
“…The mean concentrations (±1σ) of GEM, GOM, and PBM 2.5 during the entire observation period from the year 2007 to 2018 were 1.81 ± 0.43 ng m −3 (hourly mean values for 5 min intervals, N = 53,840), 1.7 ± 2.9 pg m −3 (N = 22,071) and 2.6 ± 3.6 pg m −3 (N = 22,058), respectively (Table 1). The mean GEM concentrations were lower than those reported for urban, suburban, and remote sites in the East Asian region [15,[42][43][44][45], but were slightly higher than the background concentrations recorded in the Northern hemisphere (1.3-1.6 ng m −3 ) and in the Southern hemisphere (around 1.0 ng m −3 ) [14,46]. Thus, it was inferred that the concentrations of Hg at Cape Hedo were elevated due to regional pollution because there are no local Hg stationary emission sources around this site.…”
Section: Concentrations Of Gem Gom and Pbm 25contrasting
confidence: 59%
“…Another obvious feature was that the amplitude of the RGM concentration was much greater than the GEM, and this further indicated that the RGM was easily removed from the atmosphere through both the wet and dry deposition. In addition, we found that the RGM concentrations in the nearshore area were not always higher than those in the open sea, except for the measurements in the PRE, suggesting that the RGM in the remote marine atmosphere presumably did not originate from land but from the in situ photo-oxidation of Hg 0 , which had been reported in previous studies (e.g., Hedgecock and Pirrone, 2001;Lindberg et al, 2002;Laurier et al, 2003;Sprovieri et al, 2003Sprovieri et al, , 2010Sheu and Mason, 2004;Laurier and Mason, 2007;Soerensen et al, 2010a;Wang et al, 2015).…”
Section: Spatial Distributions Of Gem and Rgmsupporting
confidence: 63%
“…Han et al, ; Y.‐J. Han et al, ; Hong et al, ; Huang, Kang, Zhang, et al, ; Huang et al, , ; Lee et al, ; Ma et al, ; Ma, Wang, Du, et al, ; Ma, Wang, Sun, et al, ; Sheu & Lin, , ; Sheu et al, , ; Song et al, ; Tang et al, ; Y. M. Wang, Peng, et al, ; Weiss‐Penzias et al, ; Xu et al, , ). GEM = gaseous elemental mercury; GOM = gaseous oxidized mercury; PBM = particulate bound mercury.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al, 2016;Ci et al, 2015;Ci, Zhang, & Wang, 2011, Ci et al, 2012Ci, Zhang, Wang, & Niu, 2011aFriedli et al, 2011;Fu, Feng, Dong, et al, 2010;Fu, Feng, Liang, et al, 2012;Fu, Feng, Shang, et al, 2012;Fu et al, 2011;Fu, Feng, Sommar, et al, 2012;Fu, Zhu, et al, 2016;Fu, Zhang, Yu, et al, 2015;Y.-J. Han et al, 2014;Hong et al, 2016;Huang et al, 2013Huang et al, , 2015Lee et al, 2016;Ma et al, 2016;Sheu & Lin, 2011Sheu et al, , 2010Song et al, 2015;Tang et al, 2018; Y. M. Wang, Peng, et al, 2014;Weiss-Penzias et al, 2015;Xu et al, 2013Xu et al, , 2015. GEM = gaseous elemental mercury; GOM = gaseous oxidized mercury; PBM = particulate bound mercury.…”
Section: Evaluation Of Model Performance Using Base-case Simulation Rmentioning
confidence: 99%